(untitled) (The Pakistan Development Review, 2004)
An attempt is made to determine the nature of land market as to how far it approximates the ideal of competitive market. It also reviews the farm size, efficiency and productivity relationship. The paper is organised in four sections. After the introductory section, the literature on past research on land markets in Pakistan and other countries is brought together in Section II. Description of land market institutions and changes in the structure of land markets including the pattern of ownership and the operational distribution of land and trends in different facets of land markets are the subject matter of Section III. Summary and conclusions are presented in the concluding section.